Koordinasi Fungsional Antar Instansi dalam Mewujudkan Kota Layak Anak (KLA) di Kota Sukabumi - Lismawati, Salma; Mulyadi, Andi; Meigawati, Dine (Jayapangus Press, 2025)
Children are a nation’s strategic asset and have the right to grow and develop in a safe, healthy, and supportive environment. The Indonesian government has issued various regulations, such as Law Number 35 of 2014 on Child Protection and Presidential Regulation Number 25 of 2021 concerning the Child-Friendly City/Regency (KLA) Policy, to ensure the protection and fulfillment of children's rights. Sukabumi City is one of the regions implementing this policy and has achieved the